CORPORATE STRATEGIC BRANDING:HOW COUNTRY AND CORPORATE BRANDS COME TOGETHER - Ðorđević, Bojan (Economic Annals, 2008)
The concept of countries as brands has been increasingly recognized in the post-modern global world. A strong country brand can provide corporate brands with a unique set of values, which supports their positioning on the international market. Simultaneously, once corporate brands achieve worldwide success, they contribute actively to developing new features of the country brand. Consumers pay more and more attention to products' country of origin. When the name of a country is mentioned, they can have positive associations (high quality, modern design, product innovation), which means that the country itself has a powerful brand. However, there are opposite cases where we talk about the weak branding of a particular country. It is necessary to mobilise all the available forces of politicians, business people, artists, sportsmen and scientists to create a strategy for enhancing the image and reputation of a country on the international markets, i.e. for creating the national branding strategy.